2022
DOI: 10.1155/2022/7621599
|View full text |Cite
|
Sign up to set email alerts
|

Stachys pilifera Benth: A Review of Its Botany, Phytochemistry, Therapeutic Potential, and Toxicology

Abstract: Background. Stachys L. (Lamiaceae) includes more than 300 annual or perennial species growing in temperate regions of Southern Africa, the Mediterranean, America, and Asia. Stachys pilifera Benth (S. pilifera), also known as Marzeh Kuhi, is an endemic species from Iran. It is found in the mountainous habitats of the Zagros area. It has various traditional uses, and the phytochemical ingredients and some biological activities of this species have been examined in previous studies. Methods. PubMed, Science Direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This activity could be attributed to phenolic and flavonoid ingredients in SPHE that produce anti-inflammatory and antioxidant effects [ 15 ]. In this line, our previous studies have reported anti-inflammatory activities and antioxidant properties of SPHE [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This activity could be attributed to phenolic and flavonoid ingredients in SPHE that produce anti-inflammatory and antioxidant effects [ 15 ]. In this line, our previous studies have reported anti-inflammatory activities and antioxidant properties of SPHE [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stachys pilifera is a perennial and fragrant plant belonging to the Lamiaceae family [ 13 ]. In traditional medicine, some Stachys species have been utilized as antinephritis, antidiarrhea, and wound disinfectants [ 14 , 15 ]. Moreover, the antibacterial, antioxidant, and cytotoxic effects of some Stachys species have been confirmed [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…(SC), Stachys byzantina K. Koch (SB), Stachys thirkei K. Koch, antibacterial activity against Gram-positive microorganisms of Stachys byzantina K.Koch, S. officinalis and S. sylvatica, nephroprotective, anti-inflammatory, hepatoprotective and anticancer properties of Stachys pilifera Benth, antiphlogistic effects of S. alpina, S. germanica, S. officinalis and S. recta antidepressant activity and apoptotic effect of Stachys pilifera Benth. [3][4][5][6][7][8][9][10][11] Antioxidant activities were mentioned for all the above species. Nutritional value was also showed by a number of studies for species such as Stachys affinis Bunge, Stachys lavandulifolia Vahl.…”
Section: Introductionmentioning
confidence: 99%